Middle cerebral artery aneurysm surgery after stent misplacement: A case report. Issue 1 (February 2016) - Al-Schameri, Abdul Rahman; Lunzer, Manuel; Daller, Cornelia; Kral, Michael; Killer, Monika
Stent misplacement during endovascular treatment of middle cerebral artery (MCA) aneurysms can cause challenges and be problematic, if clipping becomes necessary. This article reports on a 56-year-old woman with an unruptured, multi-lobulated MCA aneurysm, whom primarily refused surgery; therefore, she was scheduled for stent-assisted coiling. After successful deployment of the stent, it unfortunately then became snagged by the microcatheter and was pulled backwards. The subsequent surgical procedure (i.e. clipping of the MCA aneurysm) was challenging, due to the position of the dislodged stent. Such as misplacement of the stent is rarely documented: It resulted in the difficult handling of a MCA aneurysm. Aneurysms of the MCA should primarily be considered for surgical clipping. In conclusion, an increased risk for eventual surgery should be considered, in cases where endovascular treatments with stents are performed.